Effect of Graded Levels of Dietary Turmeric (Curcuma longa) Powder on Performance of Broiler Chicken - Singh, Pankaj Kumar (Indian Journal of Animal Nutrition, 2018)
The present study was conducted to evaluate the effect of dietary Pudina (Mentha arvensis) leaf powder on antioxidant parameters in laying hens. A total of one hundred twenty White Leghorn laying hens (36 weeks) were randomly assigned into four treatment groups (T1, T2, T3 and T4) with six replicates of five birds each. The birds were fed with different levels of pudina leaf powder at the rate of 0, 5.0, 7.5 and 10.0g /kg layer feed. At the end of fourth week of experimentation, blood was collected from two birds in each replicate to determine antioxidant parameters. The results have revealed that there is a significant (P<0.05) decreased in the level of lipid peroxidase (LPO), and significant (P<0.05) increased in reduced glutathione (GSH) and catalase (CAT) Â levels in the pudina supplemented groups. The overall best performance was observed at 10.0 g/kg level (T4 group). It can be concluded that pudina leaf powder can effectively be used as feed additive in laying hens as a strong antioxidant to protect against oxidative damage.